Optical and photoelectrical properties of lamellar gallium sulfide single crystals irradiated by γ-quanta - Madatov, R.S.; Tagiyev, B.G.; Najafov, A.I.; Tagiyev, T.B.; Gabulov, I.A.; Shakili, Sh.P. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
The influence of γ-quanta irradiation on photoelectrical and optical properties of lamellar GaS single crystals at different temperatures has been investigated. It is determined that the irradiation of pure crystals at the radiation dose equal to 30 krad results in the creation of shallow compensative acceptors, which are photoactive recombination centers (r-centers), and as a result of this both the photosensitivity and a luminescence connected with r-centers are increased. Irradiation with a radiation dose more than 100 krad results in the quenching of both photosensitivity and recombination luminescence due to formation of complexes [VGa VS]. It is proposed that radiative recombination centers arising in the course of irradiation is conditioned by sulfur hole and interstitial gallium atoms.